(untitled) - Mackey, Daphne (New York, 2006)
This book is useful for the intermediate learners. With the expansion of global business and the Internet, communicating clearly in written English has become essential. The step-by-step approach in the book allows learners to develop a core set of expressions and techniques for appropriate communication in a variety of written formats.
Keywords: English language,Ngôn ngữ tiếng Anh; Written English,Tiếng Anh viết